Bridging the Evidence Gap in Obesity Prevention: A Framework to Inform Decision Making - Institute of Medicine (The National Academies Press, 2010)
To battle the obesity epidemic in America, health care professionals and policymakers need relevant, useful data on the effectiveness of obesity prevention policies and programs. Bridging the Evidence Gap in Obesity Prevention identifies a new approach to decision making and research on obesity prevention to use a systems perspective to gain a broader understanding of the context of obesity and the many factors that influence it.
Keywords: Food and Nutrition; Health and Medicine

Framework for a National Database System for Maintenance Actions on Highway Bridges - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 668: Framework for a National Database System for Maintenance Actions on Highway Bridges explores a potential framework that provides a uniform format for collecting, reporting, and storing information on bridge maintenance actions for inclusion in a national bridge maintenance database.Appendixes A through E to NCHRP Report 668 provide detailed information on the different aspects of the research. Links to the individual appendixes are below.Appendix A: Information on Bridge Maintenance ProgramsAppendix B: National Bridge Maintenance Database TablesAppendix C: List of Element Level Costs of Maintenance ActionsAppendix D: Examples of National Bridge Maintenance Database UsesAppendix E: Other National Bridge Maintenance Database Tables
Keywords: Transportation and Infrastructure

Letter Report Assessing the USGS National Water Quality Assessment Program's Science Framework - National Research Council (The National Academies Press, 2010)
The U.S. Geological Survey requested that the National Research Council review and provide guidance on the direction and priorities of the National Water Quality Assessment (NAWQA) Program. This initial letter report concerns the scientific priorities of the NAWQA program as expressed in its NAWQA Science Framework, assessing whether the framework sets forth adequately the priorities for the future which will be addressed in the third cycle of the NAWQA program. This letter report includes guidance on the nature and priorities of current and future water quality issues that will confront the Nation over the next 10-15 years.
Keywords: Environment and Environmental Studies

Understanding Biosecurity: Protecting Against the Misuse of Science in Today's World - National Research Council (The National Academies Press, 2010)
Drawing on the work of the National Academies, this booklet introduces some of the issues at the intersection of science and security. The life sciences offer tremendous promise for meeting many 21st century challenges. But with opportunities come responsibilities. An important aspect of scientists' responsibility to society is captured in the concept of biosecurity-- the challenge to move the life sciences forward for legitimate purposes while reducing the risks that some materials, knowledge, tools, and technologies could also be used to do harm. This booklet was developed to serve as an educational resource for students and the scientific community, to illuminate the importance of biosecurity, and to explore how scientists, organizations, and governments at many levels can work together to minimize the threat.
Keywords: Policy for Science and Technology; Conflict and Security Issues

Future Directions for the National Healthcare Quality and Disparities Reports - Institute of Medicine (The National Academies Press, 2010)
As the United States devotes extensive resources to health care, evaluating how successfully the U.S. system delivers high-quality, high-value care in an equitable manner is essential. At the request of Congress, the Agency for Healthcare Research and Quality (AHRQ) annually produces the National Healthcare Quality Report (NHQR) and the National Healthcare Disparities Report (NHDR). The reports have revealed areas in which health care performance has improved over time, but they also have identified major shortcomings. After five years of producing the NHQR and NHDR, AHRQ asked the IOM for guidance on how to improve the next generation of reports. The IOM concludes that the NHQR and NHDR can be improved in ways that would make them more influential in promoting change in the health care system. In addition to being sources of data on past trends, the national healthcare reports can provide more detailed insights into current performance, establish the value of closing gaps in quality and equity, and project the time required to bridge those gaps at the current pace of improvement.
Keywords: Health and Medicine

Public Health Effectiveness of the FDA 510(k) Clearance Process: Balancing Patient Safety and Innovation: Workshop Report - Institute of Medicine (The National Academies Press, 2010)
The Food and Drug Administration (FDA) is responsible for assuring that medical devices are safe and effective before they go on the market. As part of its assessment of FDA's premarket clearance process for medical devices, the IOM held a workshop June 14-15 to discuss how to best balance patient safety and technological innovation. This document summarizes the workshop.
Keywords: Health and Medicine

Target-Setting Methods and Data Management to Support Performance-Based Resource Allocation by Transportation Agencies - Volume I: Research Report, and Volume II: Guide for Target Setting and Data Management - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 666: Target Setting Methods and Data Management to Support Performance-Based Resource Allocation by Transportation Agencies - Volume I: Research Report, and Volume II: Guide for Target-Setting and Data Management provides a framework and specific guidance for setting performance targets and for ensuring that appropriate data are available to support performance-based decision-making.Volume III to this report was published separately in an electronic-only format as NCHRP Web-Only Document 154. Volume III includes case studies of organizations investigated in the research used to develop NCHRP Report 666.NCHRP Report 706: Uses of Risk Management and Data Management to Support Target-Setting for Performance-Based Resource Allocation by Transportation Agencies was released in 2011 and supplements NCHRP Report 666. NCHRP Report 706 describes how risk management and data management may be used by transportation agencies to support management target-setting for performance based resource allocation.
Keywords: Transportation and Infrastructure

Guidebook on Risk Analysis Tools and Management Practices to Control Transportation Project Costs - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB's National Cooperative Highway Research Program (NCHRP) Report 658: Guidebook on Risk Analysis Tools and Management Practices to Control Transportation Project Costs explores specific, practical, and risk-related management practices and analysis tools designed to help manage and control transportation project costs.
Keywords: Transportation and Infrastructure

Accounting for Health and Health Care: Approaches to Measuring the Sources and Costs of Their Improvement - National Research Council (The National Academies Press, 2010)
It has become trite to observe that increases in health care costs have become unsustainable. How best for policy to address these increases, however, depends in part on the degree to which they represent increases in the real quantity of medical services as opposed to increased unit prices of existing services. And an even more fundamental question is the degree to which the increased spending actually has purchased improved health. Accounting for Health and Health Care addresses both these issues. The government agencies responsible for measuring unit prices for medical services have taken steps in recent years that have greatly improved the accuracy of those measures. Nonetheless, this book has several recommendations aimed at further improving the price indices.
Keywords: Health and Medicine; Behavioral and Social Sciences; Surveys and Statistics

Enhancing Airport Land Use Compatibility, Volume 2: Land Use Survey and Case Study Summaries - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s Airport Cooperative Research Program (ACRP) Report 27: Enhancing Airport Land Use Compatibility, Volume 2: Land Use Survey and Case Study Summaries is part of a three-volume report that explores issues related to land use around airports. Volume 2 includes 15 case studies that targeted a wide range of airports and land use issues. The case study sites include large commercial service, military, and general aviation airports and are geographically diverse. Volume 2 also provides states and local governments with examples and a common basis for establishing zoning that protects the public interest and investment in airports.Volume 1: Land Use Fundamentals and Implementation Resources provides guidance designed to help protect airports from incompatible land uses that impair current and future airport and aircraft operations and safety. Volume 3 includes aircraft accident data, a framework for an economic assessment of airport costs, and an annotated bibliography.Volume 3: Additional Resources is made up of three individual components that collectively contain some of the resource documents developed to support the information explored in Volume 1. Volume 3 includes additional detail on specific topics of aircraft accident data and third party risk, and on the economic methodology for assessing the costs associated with incompatible land uses. Volume 3 also includes an annotated bibliography that contains approximately 300 entries related to airport land use compatibility.
Keywords: Transportation and Infrastructure

A Guide for Planning and Operating Flexible Public Transportation Services - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s Transit Cooperative Research Program (TCRP) Report 140: A Guide for Planning and Operating Flexible Public Transportation Services explores the types of flexible transportation service strategies that are potentially appropriate for small, medium, and large urban and rural transit agencies. The guide examines financial and political realities, operational issues, and institutional mechanisms related to implementing and sustaining flexible transportation services.The following appendixes are available online:• Appendix A: Flexible Public Transportation Survey Respondents• Appendix B: Summary of Flexible Public Transportation Survey Responses• Appendix C: Flexible Public Transportation Services Website Information is available as an ISO image. Instructions for burning a CD-ROM from an ISO image are provided below. Help on Burning an .ISO CD-ROM Image(Warning: This is a large and may take some time to download using a high-speed connection.)
Keywords: Transportation and Infrastructure

Legal Handbook for the New Starts Process - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s Transit Cooperative Research Program (TCRP) Legal Research Digest 30: Legal Handbook for the New Starts Process explores legal issues associated with the U.S. Federal Transit Administration’s New Starts process.
Keywords: Transportation and Infrastructure

Evaluation of Biomarkers and Surrogate Endpoints in Chronic Disease - Institute of Medicine (The National Academies Press, 2010)
Many people naturally assume that the claims made for foods and nutritional supplements have the same degree of scientific grounding as those for medication, but that is not always the case. The IOM recommends that the FDA adopt a consistent scientific framework for biomarker evaluation in order to achieve a rigorous and transparent process.
Keywords: Health and Medicine

Enhancing Airport Land Use Compatibility, Volume 1: Land Use Fundamentals and Implementation Resources - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s Airport Cooperative Research Program (ACRP) Report 27: Enhancing Airport Land Use Compatibility, Volume 1: Land Use Fundamentals and Implementation Resources is part of a three-volume report that explores issues related to land use around airports. Volume 1 provides guidance designed to help protect airports from incompatible land uses that impair current and future airport and aircraft operations and safety. Volume 2: Land Use Survey and Case Study Summaries includes 15 case studies that targeted a wide range of airports and land use issues. The case study sites include large commercial service, military, and general aviation airports and are geographically diverse. Volume 2 also provides states and local governments with examples and a common basis for establishing zoning that protects the public interest and investment in airports. Volume 3 includes aircraft accident data, a framework for an economic assessment of airport costs, and an annotated bibliography. Volumes 1 and 2 are available in print and online. Volume 3 is only available in electronic format.Volume 3: Additional Resources is made up of three individual components that collectively contain some of the resource documents developed to support the information explored in Volume 1. Volume 3 includes additional detail on specific topics of aircraft accident data and third party risk, and on the economic methodology for assessing the costs associated with incompatible land uses. Volume 3 also includes an annotated bibliography that contains approximately 300 entries related to airport land use compatibility.View more information about the September 2, 2010 TRB Webinar: Enhancing Airport Land Use Compatibility, which focuses on Volume 1: Land Use Fundamentals and Implementation Resources.
Keywords: Transportation and Infrastructure

Promoting Cardiovascular Health in the Developing World: A Critical Challenge to Achieve Global Health - Institute of Medicine (The National Academies Press, 2010)
Cardiovascular disease (CVD), once thought to be confined primarily to industrialized nations, has emerged as a major health threat in developing countries. Cardiovascular disease now accounts for nearly 30 percent of deaths in low and middle income countries each year, and is accompanied by significant economic repercussions. Yet most governments, global health institutions, and development agencies have largely overlooked CVD as they have invested in health in developing countries. Recognizing the gap between the compelling evidence of the global CVD burden and the investment needed to prevent and control CVD, the National Heart, Lung, and Blood Institute (NHLBI) turned to the IOM for advice on how to catalyze change. In this report, the IOM recommends that the NHLBI, development agencies, nongovernmental organizations, and governments work toward two essential goals: creating environments that promote heart healthy lifestyle choices and help reduce the risk of chronic diseases, and building public health infrastructure and health systems with the capacity to implement programs that will effectively detect and reduce risk and manage CVD. To meet these goals, the IOM recommends several steps, including improving cooperation and collaboration; implementing effective and feasible strategies; and informing efforts through research and health surveillance. Without better efforts to promote cardiovascular health, global health as a whole will be undermined.
Keywords: Health and Medicine

Crisis Standards of Care: Summary of a Workshop Series - Institute of Medicine (The National Academies Press, 2010)
During a wide-reaching catastrophic public health emergency or disaster, existing surge capacity plans may not be sufficient to enable health care providers to continue to adhere to normal treatment procedures and follow usual standards of care. This is a particular concern for emergencies that may severely strain resources across a large geographic area, such as a pandemic influenza or the detonation of a nuclear device. Under these circumstances, it may be impossible to provide care according to the standards of care used in non-disaster situations, and, under the most extreme circumstances, it may not even be possible to provide basic life sustaining interventions to all patients who need them. Although recent efforts to address these concerns have accomplished a tremendous amount in just a few years, a great deal remains to be done in even the most advanced plan. This workshop summary highlights the extensive work that is already occurring across the nation. Specifically, the book draws attention to existing federal, state, and local policies and protocols for crisis standards of care; discusses current barriers to increased provider and community engagement; relays examples of existing interstate collaborations; and presents workshop participants' ideas, comments, concerns, and potential solutions to some of the most difficult challenges.
Keywords: Health and Medicine

Rare Diseases and Orphan Products: Accelerating Research and Development - Institute of Medicine (The National Academies Press, 2010)
Rare diseases collectively affect millions of Americans of all ages, but developing drugs and medical devices to prevent, diagnose, and treat these conditions is challenging. The Institute of Medicine (IOM) recommends implementing an integrated national strategy to promote rare diseases research and product development.
Keywords: Health and Medicine

Choosing the Nation's Fiscal Future - National Research Council (The National Academies Press, 2010)
A mismatch between the federal government's revenues and spending, now and in the foreseeable future, requires heavy borrowing, leading to a large and increasing federal debt. That increasing debt raises a serious challenge to all of the goals that various people expect their government to pursue. It also raises questions about the nation's future wealth and whether too much debt could lead to higher interest rates and even to loss of confidence in the nation's long-term ability and commitment to honor its obligations. Many analysts have concluded that the trajectory of the federal budget set by current policies cannot be sustained. In light of these projections, Choosing the Nation's Fiscal Future assesses the options and possibilities for a sustainable federal budget. This comprehensive book considers a range of policy changes that could help put the budget on a sustainable path: reforms to reduce the rate of growth in spending for Medicare and Medicaid; options to reduce the growth rate of Social Security benefits or raise payroll taxes; and changes in many other government spending programs and tax policies. The book also examines how the federal budget process could be revised to be more far sighted and to hold leaders accountable for responsible stewardship of the nation's fiscal future. Choosing the Nation's Fiscal Future will provide readers with a practical framework to assess budget proposals for their consistency with long-term fiscal stability. It will help them assess what policy changes they want, consistent with their own values and their views of the proper role of the government and within the constraints of a responsible national budget. It will show how the perhaps difficult but possible policy changes could be combined to produce a wide range of budget scenarios to bring revenues and spending into alignment for the long term. This book will be uniquely valuable to everyone concerned about the current and projected fiscal health of the nation.
Keywords: Industry and Labor; Behavioral and Social Sciences

Redesigning Continuing Education in the Health Professions - Institute of Medicine (The National Academies Press, 2010)
Today in the United States, the professional health workforce is not consistently prepared to provide high quality health care and assure patient safety, even as the nation spends more per capita on health care than any other country. The absence of a comprehensive and well-integrated system of continuing education (CE) in the health professions is an important contributing factor to knowledge and performance deficiencies at the individual and system levels. To be most effective, health professionals at every stage of their careers must continue learning about advances in research and treatment in their fields (and related fields) in order to obtain and maintain up-to-date knowledge and skills in caring for their patients. Many health professionals regularly undertake a variety of efforts to stay up to date, but on a larger scale, the nation's approach to CE for health professionals fails to support the professions in their efforts to achieve and maintain proficiency. Redesigning Continuing Education in the Health Professions illustrates a vision for a better system through a comprehensive approach of continuing professional development, and posits a framework upon which to develop a new, more effective system. The book also offers principles to guide the creation of a national continuing education institute.
Keywords: Health and Medicine; Education

Reference Guide on Understanding Common Use at Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s Airport Cooperative Research Program (ACRP) Report 30: Reference Guide on Understanding Common Use at Airports is designed to assist airports and airlines exploring the possibility of and evaluating the appropriateness of integrating “common use” in their operations. The report’s accompanying CD-ROM provides an alternative source of and approach to the information found in the reference guide and includes spreadsheet models that can be used in analyzing and evaluating how to integrate common use.“Common use” most generally refers to a technological method that airlines use to process passengers: at the ticket counter, at self-service kiosks, or at the gates. In this report, however, “common use” is also discussed as an operating philosophy that an airport can use in managing and administering the airport--representing a paradigm shift in the traditional tenant-landlord relationship.The CD-ROM is also available for download from TRB’s website as an ISO image. Links to the ISO image and instructions for burning a CD-ROM from an ISO image are provided below.Help on Burning an .ISO CD-ROM Image Download the .ISO CD-ROM Image(Warning: This is a large file that may take some time to download using a high-speed connection.)View information about the February 9, 2010 TRB Webinar, which featured this report.The October 2013 ACRP Impacts on Practice explores how the San Diego County Regional Airport Authority applied ACRP Report 30 to develop new business models for common use systems at its airport.
Keywords: Transportation and Infrastructure